2019
DOI: 10.3390/ma12071079
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Microbial Reduction of Azo Dye by Using Biochar from Iron-Rich-Biomass Pyrolysis

Abstract: Biochar is widely used in the environmental-protection field. This study presents the first investigation of the mechanism of biochar prepared using iron (Fe)-rich biomass and its impact on the reductive removals of Orange G dye by Shewanella oneidensis MR-1. The results show that biochars significantly accelerated electron transfer from cells to Orange G and thus stimulated reductive removal rate to 72–97%. Both the conductive domains and the charging and discharging of surface functional groups in biochars p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Some biochar applications require a combination of different properties to produce a significant effect [34]. One area where this happens is in processes that involve microbial electron shuttling, where many studies have reported the importance of both conductivity and redox properties for an optimal performance [64][65][66]. For example, in a recent work Prado et al [67] used biochar as an electroconductive filter material that stimulated extracellular electron transfer and microbial degradation of wastewater.…”
Section: Trade-offs Between Redox Properties and Conductivitymentioning
confidence: 99%
“…Some biochar applications require a combination of different properties to produce a significant effect [34]. One area where this happens is in processes that involve microbial electron shuttling, where many studies have reported the importance of both conductivity and redox properties for an optimal performance [64][65][66]. For example, in a recent work Prado et al [67] used biochar as an electroconductive filter material that stimulated extracellular electron transfer and microbial degradation of wastewater.…”
Section: Trade-offs Between Redox Properties and Conductivitymentioning
confidence: 99%
“…The dye, pigment and textile industries are those which has great outcome of income and adds to economic growth of all countries to the world [1]. Azo dyes constitute about 70% of the whole dye family and hence an important dye [2] among all. Adsorption of dyes on biochar from aqueous solution is the most frequently used technique for wastewater treatment and it's a cost savour treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increasing attention has been paid to the harmful pollution of industrial organic dyes to our water bodies. In the past several decades, numerous research works have been done to reduce their hazardous effects, including the physical adsorption of activated carbon and clay [ 4 , 5 ], biodegradation [ 6 ], chemical degradation by advanced oxidation process [ 7 , 8 , 9 , 10 ] and degradation of specific alloys [ 11 , 12 , 13 , 14 ]. However, these methods have obvious disadvantages such as low-efficiency, high-cost and short service life.…”
Section: Introductionmentioning
confidence: 99%